Bilateral Basal Ganglia Calcification: The Etiology and Clinical Findings of 17 Patients - Aylin Akçalı; Sırma Geyik; Münife Neyal (Türk Nöroloji Dergisi, 2009)
OBJECTIVE: Bilateral basal ganglia calcification is a rare disease with symmetrical and bilateral deposition of calcium and other minerals in the basal ganglia, cerebellum, dentate nucleus, and white matter. Clinical findings are variable and can present with psychiatric symptoms, epileptic seizures, cerebellar features, extrapyramidal dysfunction, and dementia. Parathyroid pathologies as well as other metabolic disorders are the main etiologic causes of bilateral basal ganglia calcification. METHODS: In this article, we retrospectively analyzed the etiologic and clinical findings of 17 (nine famale, eight male) patients diagnosed with bilateral basal ganglia calcification between 2002 and 2008 in Gaziantep University, Faculty of Medicine, Department of Neurology outpatient clinic. RESULTS: Clinical features were variable. Four patients had headache, six seizures, five speech disorder, four movement disorders, and four forgetfulness and psychiatric problems. Nine of 17 patients had hypoparathyroidism in the etiology of bilateral basal ganglia calcification. The involvements of basal ganglia and the thalamus were the most frequent findings in cranial imagings. CONCLUSION: Hypoparathyroidism and thalamus involvement were found frequently. The detection of bilateral basal ganglia calcification on imaging may be helpful in the diagnosis and treatment of underlying diseases and thus can be considered an important finding